PENGARUH INOVASI PRODUK , PERSEPSI HARGA DAN PROMOSI TERHADAP KEPUASAN PELANGGAN (Studi Pada Konsumen Produk Batik Tulis Bakaran Di Kabupaten Pati) - Mugiarto, 13.05.51.0149; Sutejo, Bambang (Students' Journal of Economic and Management, 2017)
This study aims to identify and analyze the effect of product innovation, price perception and promotion of consumer satisfaction in Product Purchase Batik Bakaran Pati regency. This study uses primary data by the method of data collection by questionnaire. A sample of 100 respondents, using a sampling technique in this study using purposive sampling sampling with criteria that consumers who have never purchased Batik Bakaran Pati regency. Methods of data analysis using linear regression. The test results showed that the positive effect of product innovation to customer satisfaction, perception of price positive effect on customer satisfaction and the promotion of a positive effect on customer satisfaction. Overall the research model is said to be fit or worthy as a research model with determination coefficient value close to 1. Keywords: product innovation, the perception of price, promotion and customer satisfaction